Pelaksanaan Perilaku Hidup Bersih dan Sehat (PHBS) pada Pelayanan Kesehatan Masyarakat di Puskesmas Tuntungan 1 Kecamatan Pancur Batu Kabupaten Deli Serdang - Meilisa Luthfiah; Zuhrina Aidha; Saski Amalia Khairunnisa; Siti Aminah; Yunita Anggraini; Zukhaira Hayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Clean and Healthy Living Behavior (PHBS) are all health behaviors that are carried out out of awareness so that family members or families can help themselves in the health sector and can play an active role in health activities and play an active role in health activities in the community. The purpose of this study was to find out how to implement clean and healthy behavior (PHBS) in public health services at the Tuntungan 1 Health Center, Pancur Batu District, Deli Serdang Regency. As well as describe and describe the implementation of public health services. The type of research used was descriptive qualitative research. Data collection was obtained in the form of primary data. The data were obtained directly from informants (informants) by means of interviews. In determining informants, researchers used incidental sampling, namely employees who work in health services. Key informants used a purposive sampling technique in which information or data was collected by selecting informants who were considered competent to become data sources. From the results of the study it can be seen that several PHBS programs have been running as they should, but there are still some obstacles they face, namely the lack of health facilities and the insufficient number of health and cleaning staff. Keywords: Puskesmas, PHBS, Health Services